Sugarcane green ceramic hollow fibre membrane for oily wastewater separation - Jamalludin, Mohd Riduan (2018)
Oily wastewater is one of the greatest problems in the world and needs an urgent solution. Therefore, this work describes the preparation of green ceramic hollow fiber membranes derived from waste sugarcane bagasse ash (WSBA) using phase inversion and sintering techniques. The first step in the production of WSBA was the calcination process of sugarcane bagasse at 800 °C followed by characterization of the microstructure, phases present, and thermal behavior using transmission electron microscopy (TEM), X-ray fluorescence (XRF), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR). This process was followed by the preparation of ceramic dope suspension consisting of WSBA powder as the main material, NMP as the solvent, PESf as the binder, and Arlacel P135 as the dispersant. In this work, various spinning parameters (effect of WSBA contents, bore fluid flow rate, air gap, and sintering temperature) were evaluated. By varying these parameters, significant effects on the membrane structure and mechanical strength were observed. The preliminary performance tests show that the green ceramic hollow fiber membrane prepared with a WSBA content of 60 wt%, bore fluid flow rate of 10 mL/min, air gap of 10 cm, and sintering temperature of 1000 °C induced a stable permeate water flux (PWF) of ~466.2 L/m2h at the beginning of the filtration process. The investigation was further towards development of superhydrophobic and superoleophilic green ceramic hollow fibre membrane (ss-CHFM/WSBA) grafted with TEOS and MTES through sol-gel method for separation oily wastewater. Various grafting parameters such effect of grafting time, grafting cycle and calcination temperature were conducted towards membrane performance and morphology. The newly-developed ss-CHFM/WSBA induced excellent wettability properties with contact angle value of 161.1° at 60 min of grafting time, 3 cycle of grafting cycle and calcination temperature at 400 °C. In addition, it was also found that these parameters gave evenly nano-silica particle distribution on the surface. As a result, excellent oil flux (134.2 L/m2h ) and oil separation efficiency (99.9%). Therefore, the optimization of oil condition in term of pH, oil concentration and oil temperature on the ss-CHFM/WSBA performance (oil flux and oil separation efficiency) was evaluated by using response surface methodology (RSM). The optimum ss-CHFM/WSBA performance was predicted at pH 10, 10.01 ppm for oil concentration and 69.04 °C for oil temperature. The verification result was found in acceptable average error at 4.71% for oil flux and 0.746% for oil separation efficiency.